The Mediating Role of Early Maladaptive Schemas in Explaining the Causal Relationships Between Childhood Maltreatment, Attachment Styles, and Forgiveness in Betrayal Victims - Mahmoudvand, Mohsen; Zahrakar, Kianoush; Hasani, Jafar (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The primary goal of this study was to present a forgiveness model based on childhood maltreatment and attachment styles, with the mediating role of early maladaptive schemas in betrayal victims. Methods: This descriptive correlational study involved betrayal victims who had sought counseling in Tehran in 2022, with a sample of 653 individuals selected through convenience sampling. The instruments used included Bernstein et al.’s (2003) Childhood Trauma Questionnaire, Hazan and Shaver’s (1987) Attachment Style Questionnaire, Young’s (1999) Early Maladaptive Schema Questionnaire, and the Forgiveness Questionnaire by Ray et al. (2001). Data were analyzed using SPSS version 25 and AMOS version 24. Findings: The results indicated a negative relationship between childhood maltreatment, insecure attachment styles, and early maladaptive schemas with forgiveness, while secure attachment showed a positive relationship with forgiveness. Furthermore, the results suggested that early maladaptive schemas mediated the relationship between childhood maltreatment, attachment styles, and forgiveness in betrayal victims. Conclusion: Overall, the results indicated that the evaluated structural model was well-fitted, and the findings could assist therapists and counselors in better understanding the forgiveness process in betrayal victims.